Impact of Reducing the Procedure Time on Thromboembolism After Coil Embolization of Cerebral Aneurysms - Lee, Sang-Hwa; Jang, Min Uk; Kang, Jihoon; Kim, Yeo Jin; Kim, Chulho; Sohn, Jong-Hee; Yang, Jinseo; Jeon, Jin Pyeong; Cho, Yongjun; Choi, Hyuk Jai (Frontiers in Neurology, 2018)
Background: There is still controversy regarding which procedure-related factors affect the occurrence of periprocedural thromboembolism. This study aimed to investigate which procedure-related risk factors can be modified to prevent adverse thromboembolic events after coil embolization of intracranial aneurysm. Methods: Using a single-center database, we retrospectively identified a consecutive series of patients with symptomatic and asymptomatic cerebral aneurysms treated with coil embolization. We evaluated the following procedure-related factors: procedure time, procedure methods (simple coiling, stent-assisted coiling, and use of multiple microcatheters), and number of coils inserted. The primary outcome was the development of thromboembolism before and after coil embolization confirmed by diffusion-weighted imaging (DWI) irrespective of the location of the procedure. Pearson's chi-square, Student's t-test, multivariable logistic regression analysis, and sensitivity analysis with multinomial logistic regression analysis were used in the statistical analyses. Results: Of 180 cases enrolled, 146 (81.1%) had evidences of thromboembolism confirmed by DWI, and 13 (7.2%) had neurologic symptoms. Among the documented modifiable procedure-related factors, every 10 min increase in the procedure time was independently associated with the risk of thromboembolism, after adjusting the analysis (adjusted odds ratio 1.11; 95% confidence interval 1.01–1.21). The coiling methods, use of multiple catheters, and number of coils inserted did not change the effect of the procedure time on thromboembolic events (p for interactions > 0.05). Conclusion: This study showed that the procedure time might be the most effective modifiable factor for reducing thromboembolic events irrespective of the procedure methods used during coil embolization of cerebral aneurysms.